2022
DOI: 10.3390/en16010070
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy, Growth, Financial Development and Renewable Energy in Romania: An Autoregressive Distributed Lag Model with Evidence for Growth Hypothesis

Abstract: This research aims to identify the influence of fiscal policy, financial development and economic growth on the increase of renewable consumption in Romania. To achieve our objective, we employ bivariate regressions through the Autoregressive Distributed Lag method, over the 2000–2020 period, to examine these influences. We find clear evidence that the variables observed (implicit tax rate on energy, external debt stocks, real GDP per capita, environmental tax revenues from energy taxes, and market capitalisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The coefficients of @CUMDP(FD) and @CUMDN(FD) are both positive and significant, which implies that (FD) has a positive and lasting impact on GDP per capita, regardless of whether it increases or decreases. Our finding that FD has a positive effect on EG aligns with previous studies such as Al Khatib et al (2022), who found a similar relationship for Syria, and Doran et al (2022), who demonstrated that FD has a positive effect on EG in developing countries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The coefficients of @CUMDP(FD) and @CUMDN(FD) are both positive and significant, which implies that (FD) has a positive and lasting impact on GDP per capita, regardless of whether it increases or decreases. Our finding that FD has a positive effect on EG aligns with previous studies such as Al Khatib et al (2022), who found a similar relationship for Syria, and Doran et al (2022), who demonstrated that FD has a positive effect on EG in developing countries.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, Al Khatib et al (2022) revealed a statistically significant positive impact of FD on EG in Syria. Doran et al (2022) demonstrated that FD has a positive effect on EG in developing countries. However, the magnitude of this influence changes with different measures of FD, estimation technique, data periodicity, and the mathematical form of the nexus, as reported by Khan and Senhadji (2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emission reductions are mainly due to the following factors: taxation; the increased penetration of renewable energy (especially biomass and wind); carbon capture; and storage technologies for fossil fuels and/or biomass. Doran et al [22] identified the influence of fiscal policy, financial development and economic growth on the increase in the consumption of renewable sources in Romania using the Autoregressive Distributed Lag method in the period 2000-2020. The external debt stocks; real GDP per capita; and implicit tax rate on energy variables have a sig-nificant positive influence on the consumption of renewable energy, while the market capitalization of listed domestic companies and environmental tax revenues from energy taxes independent variables have a significant negative impact on the dependent variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 37 ]. showed no threshold beyond which EG is negatively affected [ 38 ]. found positive effects on developing country EG Ref.…”
Section: Literature Reviewmentioning
confidence: 99%